2013
DOI: 10.1158/1535-7163.mct-13-0459
|View full text |Cite
|
Sign up to set email alerts
|

The Novel VEGF Receptor/MET–Targeted Kinase Inhibitor TAS-115 Has MarkedIn VivoAntitumor Properties and a Favorable Tolerability Profile

Abstract: VEGF receptor (VEGFR) signaling plays a key role in tumor angiogenesis. Although some VEGFR signaltargeted drugs have been approved for clinical use, their utility is limited by associated toxicities or resistance to such therapy. To overcome these limitations, we developed TAS-115, a novel VEGFR and hepatocyte growth factor receptor (MET)-targeted kinase inhibitor with an improved safety profile. TAS-115 inhibited the kinase activity of both VEGFR2 and MET and their signal-dependent cell growth as strongly as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…2E). Previous studies have found that HGF plays a significant role in tumor angiogenesis and induces VEGF expression in tumor cells [12][13][14][15]. A sketch map about HGF and its relationship with VEGF pathway is summarized in Fig.…”
Section: Hgf Is Validated As a Direct Target Of Mir-26a/b And Correlamentioning
confidence: 99%
“…2E). Previous studies have found that HGF plays a significant role in tumor angiogenesis and induces VEGF expression in tumor cells [12][13][14][15]. A sketch map about HGF and its relationship with VEGF pathway is summarized in Fig.…”
Section: Hgf Is Validated As a Direct Target Of Mir-26a/b And Correlamentioning
confidence: 99%
“…A combination of golvetanib and lenvatinib (VEGF and RET inhibitor) was able to overcome HGF-induced resistance in human primary cell cultures and cell lines, but further studies are needed to validate these results [185]. TAS-115 and T-1840383 are dual MET/VEGFR inhibitors that have shown in vitro and in vivo antiproliferative activity by blocking angiogenesis, with no toxic effects [186,187].…”
Section: Non-selective Met Inhibitorsmentioning
confidence: 99%
“…TAS-115 suppresses FMS-dependent signal in pre-osteoclasts and osteoclasts by inhibiting the phosphorylation of FMS. Several targets for TAS-115 were identified in a ProfilerPro kinase screen (4). However, it is well known that null mutation of FMS induces osteopetrosis because of the lack of osteoclast in op/op mice (20).…”
Section: Discussionmentioning
confidence: 99%
“…PC3 cells were cultured in RPMI 1640 medium with 10% FBS at 37°C under 5% CO 2 in air. TAS-115, a VEGFR/ MET-targeted kinase inhibitor, was prepared by Taiho Pharmaceutical Co., Ltd. (Tokyo Japan) as reported previously (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation